PEMBERDAYAAN MASYARAKAT NGEPAS KIDUL MELALUI BUDI DAYA JAHE (NGEPAS KIDUL DONOHARJO, SLEMAN, DI YOGYAKARTA) - Sunarno -; Putri Anggia (Department of Agricultural Product Technology, Faculty of Agricultural Technology, Universitas Andalas Kampus Limau Manis - Padang, Sumatera Barat Indonesia-25163, 2019)
Keberdayaan masyarakat petani dalam berbagai aspek di era milenial adalah sangat dibutuhkan. Kelompok masyarakat petani di berbagai sektor Pertanian termasuk Pertanian jahe dituntut untuk berdaya dari aspek Pengetahuan, SDM dan Kelembagaan dan jaringan pemasaran. Program PPM ini bertujuan untuk memberikan upaya pemberdayaan di berbagai aspek berupa menambah pengetahan dan skill, memperkuat kelembagaan, dan memberikan pendampingan dalam rangka ekspansi jaringan pasar. Metode program ini adalah dengan pola penyuluhan, motivasi, pelatihan dan pendampingan sehingga tujuan dari program ini tercapai. Hasil dari program ini bahwa keberdayaan pada aspek pengetahun dan skill dengan metode penyluruhan telah berhasil walaupun belum maksimal, pemberdayaan kelembagaan sudah dipahami dan dilaksanaan melalui penguatan kelompok kelompok tani misalnya kelompok tani wanita, sedangkan penguatan kelembagaan dalam bentuk badan hukum baru tahap persiapan dan melengkapi anggaran dasar dan anggaran rumah tangga (AD/ART). Begitu pula produk jahe sementara ini baru sebatas membuat trade merk, untuk sampai ke hak paten masih perlu dipersiapkan syarat syarat administrasi dan syarat teknis dan klinis. Kata kunci: Budidaya jahe, Jahe, Pemberdayaan masyarakat, Kelompok petani ABSTRACT The empowerment of farmers in various aspects of the millennial era is very much needed. Farmer groups in various agricultural sectors, including ginger farming, are required to be empowered from the aspects of Knowledge, H, and Institution and network marketing. The PPM program aims to provide empowerment efforts in various aspects in the form of increased knowledge and skills, strengthening institutions, and providing assistance to expand the market network.The method of this program is with patterns of counseling, motivation, training, and assistance so that the objectives of this program was achieved. The results of this program are that empowerment in the aspects of knowledge and skills. The method of overall success has been done even though it has not been maximized; institutional empowerment has been understood and implemented through strengthening farmer groups such as women's farmer groups while strengthening institutions in the form of new legal entities preparation and completing articles of association and by-laws (AD / ART). Similarly, ginger products, while only limited to making brand trade, to get to the patent rights still need to be prepared for terms of administrative requirements and technical and clinical requirements. Keywords: Cultivating ginger, Ginger, Community empowerment, Farmer Groups